2017
DOI: 10.5306/wjco.v8.i3.261
|View full text |Cite
|
Sign up to set email alerts
|

Levels of neutrophil gelatinase-assosciated lipocalin in patients with head and neck squamous cell carcinoma in Indian population from Haryana state

Abstract: AIMTo study the levels of neutrophil gelatinase associated lipocalin (NGAL) in head and neck squamous cell carcinoma (HNSCC).METHODSThis was a non randomized case control study conducted at Department of Biochemistry, in collaboration with Regional Cancer Center over a period of one year. The study population included 50 adult newly diagnosed HNSCC patients reporting in outpatient department at Regional Cancer Center and compared with 50 healthy controls. NGAL was estimated by ELISA technique. Student t test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Interestingly, the expression of both LNC2 and MMP9 genes was increased in 16 tumor types, demonstrating Frontiers in Cell and Developmental Biology frontiersin.org their involvement in tumor development. This result was consistent with those reported in the literature for several tumors, including BLCA (Ricci et al, 2015;Candido et al, 2016b), CESC (Li et al, 2012), CHOL (Leelawat et al, 2011;Nair et al, 2018;, ESCA (Zhang et al, 2007), HNSC (Ruokolainen et al, 2005;Hiromoto et al, 2011;Stanciu et al, 2016;Verma et al, 2017), KIRP (Cho et al, 2003;Zhang et al, 2015), LIHC (Chen et al, 2012;Abdelsameea et al, 2020), LUAD (Ruiz-Morales et al, 2015), OV (Cho and Kim, 2009;Gupta et al, 2022); PAAD (Kaur et al, 2013), STAD (Du et al, 2011), UCEC (Cymbaluk-Płoska et al, 2017), COAD (Yang et al, 2014;Ozemir et al, 2016;Liang and Chang, 2018), LUSC (Lee et al, 2015), PRAD (Ma et al, 2017;Muşlu et al, 2017;Ulusoy et al, 2021), READ (Zhang et al, 2009;Annaházi et al, 2016), and THCA (Barresi et al, 2012;Liu et al, 2019;Xu et al, 2019). Despite many authors reporting that LNC2 and MMP9 were widely associated with worse prognosis in several tumors, our in silico analysis revealed that the OS and PFI were simultaneously negatively affected by both genes only in KIRC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the expression of both LNC2 and MMP9 genes was increased in 16 tumor types, demonstrating Frontiers in Cell and Developmental Biology frontiersin.org their involvement in tumor development. This result was consistent with those reported in the literature for several tumors, including BLCA (Ricci et al, 2015;Candido et al, 2016b), CESC (Li et al, 2012), CHOL (Leelawat et al, 2011;Nair et al, 2018;, ESCA (Zhang et al, 2007), HNSC (Ruokolainen et al, 2005;Hiromoto et al, 2011;Stanciu et al, 2016;Verma et al, 2017), KIRP (Cho et al, 2003;Zhang et al, 2015), LIHC (Chen et al, 2012;Abdelsameea et al, 2020), LUAD (Ruiz-Morales et al, 2015), OV (Cho and Kim, 2009;Gupta et al, 2022); PAAD (Kaur et al, 2013), STAD (Du et al, 2011), UCEC (Cymbaluk-Płoska et al, 2017), COAD (Yang et al, 2014;Ozemir et al, 2016;Liang and Chang, 2018), LUSC (Lee et al, 2015), PRAD (Ma et al, 2017;Muşlu et al, 2017;Ulusoy et al, 2021), READ (Zhang et al, 2009;Annaházi et al, 2016), and THCA (Barresi et al, 2012;Liu et al, 2019;Xu et al, 2019). Despite many authors reporting that LNC2 and MMP9 were widely associated with worse prognosis in several tumors, our in silico analysis revealed that the OS and PFI were simultaneously negatively affected by both genes only in KIRC patients.…”
Section: Discussionsupporting
confidence: 92%